1996
DOI: 10.1007/bf00335707
|View full text |Cite
|
Sign up to set email alerts
|

Liver graft-transmitted glioblastoma multiforme. A case report and experience with 13 multiorgan donors suffering from primary cerebral neoplasia

Abstract: The transmission of donor-related malignancies by organ transplantation is a rather rare event. There has only been one report on the development of a brain tumor metastasis in liver transplantation. From September 1988 to January 1993, 342 donor hepatectomies with subsequent transplantation were performed at our center. The main donor diagnoses included subarachnoidal bleeding (n = 128; 37.4%), isolated head injury (n = 114; 33.3%), multiple injuries (n = 55; 16.1%), primary cerebral neoplasia (n = 13; 3.8%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…These cases have included donor transmitted neuroendocrine carcinoma (13), Kaposi's sarcoma (17), leiomyosarcoma (16), melanoma (11), adenocarcinomas (18,26), glioblastomas (15,27,28), and choriocarcinomas (12,14,24,25) Our case represents such a case and, to our knowledge, is the only reported case of donor-transmitted SCC occurring in a transplanted liver. Epidermoid cancers have been reported to be transmitted to renal recipients (29).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…These cases have included donor transmitted neuroendocrine carcinoma (13), Kaposi's sarcoma (17), leiomyosarcoma (16), melanoma (11), adenocarcinomas (18,26), glioblastomas (15,27,28), and choriocarcinomas (12,14,24,25) Our case represents such a case and, to our knowledge, is the only reported case of donor-transmitted SCC occurring in a transplanted liver. Epidermoid cancers have been reported to be transmitted to renal recipients (29).…”
Section: Discussionmentioning
confidence: 85%
“…There have been very few documented cases of nonlymphoid solid organ tumors of donor origin reported following liver transplantation (11)(12)(13)(14)(15)(16)(17)(18)(24)(25)(26)(27)(28). These cases have included donor transmitted neuroendocrine carcinoma (13), Kaposi's sarcoma (17), leiomyosarcoma (16), melanoma (11), adenocarcinomas (18,26), glioblastomas (15,27,28), and choriocarcinomas (12,14,24,25) Our case represents such a case and, to our knowledge, is the only reported case of donor-transmitted SCC occurring in a transplanted liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penn 84 noted that 117 of 270 recipients of organs from donors with malignancies developed cancer. Jonas et al 85 reported the transmission of a single glioblastoma multiforme of 49 organs transplanted from donors with central nervous system malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…If the assessment of a graft was considered to be critical, the decision was objectified with a frozen section biopsy. Primary malignancy of the donor -except for selected cases of primary cerebral neoplasiawas an exclusion criterion [5].…”
Section: Methodsmentioning
confidence: 99%